Magnesium uptake dynamism of maize (Zea mays L.) on prairie soil - Sipos, Marianna (Acta Agraria Debreceniensis, 2010)
Different influence factors on the magnesium (Mg) uptake in case of three maize hybrids with different long vegetation period have been investigated at the Experimental Station of the University of Debrecen, Centre of Agricultural Sciences and Engineering, at Debrecen-Látókép. The soil of the experiment is a calcareous chernozem, based on loess, with high fertility, that is characteristic for soils of the region Hajdúság. Upon irrigation is the experiment divided to main plots, by different hybrids into sub-plots, while treatments of five nutrientsupply levels with fixed N:P2O5:K2O rate (beside control)mean sub-subplots. Soil samples were taken from the upper, cultivated soil layer 3 times during the year 2008. Their pH has been measures in a 0.01 M CaCl2-solution and their Mg-content from the same solution and from ammonium-lactate acetic acid (AL) extract. Plant samples were taken seven times in the vegetation period, of which we measured the Mg-content. Beside this, the during the vegetation period by maize biomass extracted Mg-amount has been calculated using fresh and dry matter weights. The effects of irrigation, hybrids and nutrient-supply levels on the soil pH and on the AL- and CaCl2-extractable Mg-amount have been studied, as well. After that I tried to find a correlation between soil pH and the Mg-content of soil determined in different extractants, beside this between the by the two solutions extracted Mg-amount.